Reading Egyptian art : a hieroglyphic guide to ancient Egyptian painting and sculpture - Wilkinson, Richard H. (London : Thames and Hudson, 1992)
The art of ancient Egypt has excited imaginations for centuries. But without knowledge of hieroglyphic images, Egypt's rich artistic legacy, from colossal statues to finely wrought jewelry and minuscule charms, remains obscure. Here, for the first time, is an introduction to the symbolic language of hieroglyphs: a directory of the one hundred signs used most often in Egyptian painting and sculpture--from seated man and lion to vulture and ankh. This great repertoire of.
symbols was developed to make the trancendental enigmas of creation, fortune and fecundity, death and the life beyond, immediate and understandable. Richard Wilkinson's authoritative and thoroughly researched guide offers a comprehensive explanation of the symbols, their origins, identification and uses. He shows how they form a crucial pictorial component of many of the greatest Egyptian masterpieces--an insight hitherto enjoyed only by scholars and Egyptologists. The.
hieroglyphs are arranged thematically, fully cross-referenced, and illustrated by several hundred newly commissioned drawings and photographs. The result is an indispensable companion for those seeking to understand the mysteries of Egyptian art, and a fascinating sourcebook for all ages on an ancient language's hidden symbols and signs.
Man -- Woman -- Anthropomorphic deities -- Parts of the human body -- Mammals -- Parts of mammals -- Birds -- Parts of birds -- Amphibians and reptiles -- Fishes and parts of fishes -- Invertebrates -- Trees and plants -- Sky, earth, water -- Buildings and parts of buildings -- Ships and parts of ships -- Domestic and funerary furniture -- Temple furniture and sacred emblems -- Crowns, dress, staves -- Warfare, hunting, butchery -- Agriculture and crafts -- Rope, fiber, baskets -- Vessels of stone and earthenware -- Loaves and cakes -- Writings, games, music.
Includes bibliographical references (p. 220-222) and index.
Keywords: Art, Egyptian -- Themes, motives; Art, Ancient -- Egypt -- Themes, motives; Symbolism in art -- Egypt; Egyptian language -- Writing, Hieroglyphic; Visual arts -- History; Egypt